An evaluation of mobile Quran apps - Mahmud, Murni; Abubakar, Adamu (2015)
The fact that mobile Quran apps are widely available for almost all Smartphone platforms, justify the need for this particular study, which seek to investigate the state and current design and content features of mobile Quran. The study was undertaking by content analysis through single-user evaluation. The reason for using this research methodology is because it is objective, systematic and quantitative and tends to emphasize on procedure rather than critical examination of data only. Sample of 10 mobile Quran were extracted randomly from the Internet and evaluated. The result express the credits given by users through Google Plus like rating, the effect of the design and features of each, together with the validation status.